Do socioeconomic factor affect on the quality of life of Malaysian fishermen? - Jumadil Saputra, Norizan Abdul Ghani, Fadzli Adam,; Dara Aisyah H.M. Ali Puteh, Berhanundin Abdullah (Opción, 2019)
This study is written to propose new indicators for measuring the quality of life and examine socioeconomic factor, and government policy could be improving the living standard of fishermen. This study designed using quantitative and qualitative approaches through cross-sectional study. The result of this study showed that socioeconomic factor has significant for improving the quality of life of Malaysian fishermen. In conclusion, religious programs should also be enhanced in the fishing community, especially to the second generation of fishermen.